Effectiveness of Outpatient Chronic Pain Management for Middle-Aged Patients by Internet Hospitals: Retrospective Cohort Study - Ling Sang; Bixin Zheng; Xianzheng Zeng; Huizhen Liu; Qing Jiang; Maotong Liu; Chenyu Zhu; Maoying Wang; Zengwei Yi; Keyu Song; Li Song (JMIR Medical Informatics)
Abstract BackgroundChronic pain is widespread and carries a heavy disease burden, and there is a lack of effective outpatient pain management. As an emerging internet medical platform in China, internet hospitals have been successfully applied for the management of chronic diseases. There are also a certain number of patients with chronic pain that use internet hospitals for pain management. However, no studies have investigated the effectiveness of pain management via internet hospitals. ObjectiveThe aim of this retrospective cohort study was to explore the effectiveness of chronic pain management by internet hospitals and their advantages and disadvantages compared to traditional physical hospital visits. MethodsThis was a retrospective cohort study. Demographic information such as the patient’s sex, age, and number of visits was obtained from the IT center. During the first and last patient visits, information on outcome variables such as the Brief Pain Inventory (BPI), medical satisfaction, medical costs, and adverse drug events was obtained through a telephone follow-up. All patients with chronic pain who had 3 or more visits (internet or offline) between September 2021, and February 2023, were included. The patients were divided into an internet hospital group and a physical hospital group, according to whether they had web-based or in-person consultations, respectively. To control for confounding variables, propensity score matching was used to match the two groups. Matching variables included age, sex, diagnosis, and number of clinic visits. ResultsA total of 122 people in the internet hospital group and 739 people in the physical hospital group met the inclusion criteria. After propensity score matching, 77 patients in each of the two groups were included in the analysis. There was not a significant difference in the quality of life (QOL; QOL assessment was part of the BPI scale) between the internet hospital group and the physical hospital group (PPPPPPPP ConclusionsInternet hospitals are an effective way of managing chronic pain. They can improve patients’ QOL and satisfaction, reduce treatment costs, and can be used as part of a multimodal strategy for chronic pain self-management.